Regionalization and the special Autonomous Regions political and institutional issues - Valdehuesa, Manuel E. Jr (Philippine Journal of Public Administration, 1988)
In the search for the appropriate political and administrative model for the autonomous regions, the Aquino government and the separatist Muslims of the Southern Philippines find themselves in some kind of a tug-of-war. However, some common ground exists between the government and the rebels in Mindanao based on the Tripoli Agreement, which guarantees autonomy, although varying and opposing interpretations of the Agreement by the concerned parties give rise to a deadlock in the negotiations. The Aquino government should therefore continue to endeavor attempts to find the necessary compromise along constitutional and democratic lines.